ANALISIS METODE SEROLOGI WIDAL LAPANGAN, WIDAL PEMBANDING, DAN KULTUR PADA PENDERITA SUSPEK DEMAM TIFOID DI SULAWESI SELATAN - Syamsu Rijal (As-Syifaa Jurnal Farmasi, 2014)
The aim of the study was to discover the difference of field widal and comparative widal in detecting Salmonella typhi in typhoid suspect patient, sensitivity, specificity, positive and negative prediction scores of Widal and to culture. The study was conducted at the Biomolecular and Immunology Laboratory of the faculty of Medicine Hasanuddin University. The number of samples was 40 typhoid suspect patiens colleted from examination of field Widal at public health centers and hospitals in south Sulawesi. The serum samples of the patient were reexamined by using Widal comparative methods, and culture examination was done to blood sample. The results of the study indicate that comparative widal sensitivity 70%, spesificity 26%, positive predictive score 24,1%, negative predictive score 16,7%, and filed Widal sensitivity 30%, specificity 30%, positive predictive score 16,7%, and negative predictive score 68,2%. The comparative Widal has higher sensitivity than field Widal.